Nghiên cứu các yếu tố ảnh hưởng đến ý định tiếp tục mua Thực phẩm tươi sống của Gen Z trên sàn thương mại điện tử trong thời điểm bình thường mới - Lê Thị Hồng , Minh; Phạm Thế , Cường; Bùi Thị Diệu , Hiền; Nguyễn Thị Quỳnh , Linh; Nguyễn Hoài , Nhi; Vi Đức , Hùng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
The widespread COVID-19 epidemic has led to online shopping on e-commerce platforms becoming superior because people are restricted from traveling during social distancing. As a result, consumers' demand for food and goods has increased sharply. However, in the current "New Normal," will they still choose to buy online or return to the traditional forms of before? This study explores the factors affecting the intention to continue buying fresh food on the e-commerce platform of genZ. The study used both qualitative and quantitative methods. Two hundred eighty-nine valid samples were collected online, and SPSS software was used to analyze the research model. The results show that variables such as habit, product quality, and product price affect the intention to buy fresh food on e-commerce platforms. This result helps administrators find solutions to attract customers to continue buying food on e-commerce platforms in the new normal.
Keywords: Fresh foods; Online shopping; New routine; UTAUT2; Intention to keep buying; Post-pandemic habits